A superior low-cost amorphous carbon anode made from pitch and lignin for sodium-ion batteries. Issue 1 (24th November 2015) - Li, Yunming; Hu, Yong-Sheng; Li, Hong; Chen, Liquan; Huang, Xuejie
Abstract : This study reports a superior low-cost amorphous carbon anode made from pitch and lignin with excellent electrochemical performance for sodium-ion batteries for the first time. Abstract : Sodium-ion batteries (SIBs) are a promising candidate for grid electricity storage due to their potential low cost. The development of anode materials is a crucial step to promote the commercialization of SIBs, and amorphous carbon materials are likely to be the most promising alternatives among all proposed anode materials. However, the cost of the reported carbon materials is still very high due to the expensive precursors and their low carbon yield. Here, we report an amorphous carbon (AC) material made from low cost pitch. The amorphous carbon material with an amazing high carbon yield of 57% was achieved by utilizing the emulsification interaction between pitch and lignin to suppress the graphitization of pitch during the carbonization. The effects of heat-treatment temperatures and the pitch/lignin mass ratios on the morphology, microstructure and the electrochemical performance of AC were systematically investigated. By optimizing experimental conditions, we achieved one representative AC with a suitable morphology and microstructure, which exhibits promising performances with a high reversible capacity of 254 mA h g −1, a high initial coulombic efficiency of 82% and excellent cycling stability. This is the first demonstration that the pitch can be successfully applied in fabricating amorphous carbon anode materials for SIBs with superior low cost and high performance.